Measuring the effects of commodity price shocks on Asian economies - Tomoo Inoue; Tatsuyoshi Okimoto (Asian Development Bank Institute (ADBI), 2017)
Commodity prices have become volatile over the past 2 decades, and their recent sharp decline has decreased the consumer price index inflation rates for most economies. While many Asian economies have benefited from low international oil and food prices, commodity exporters have suffered. Thus, the negative impact on production through the decline of producer prices has attracted considerable attention. Given this situation, policy makers have become increasingly concerned about measuring the magnitude of oil and food price shock diffusion on a country's various inflationary indicators. This study investigates this problem by using a Global Vector Autoregressive model. We extend the work by Galesi and Lombardi (2009), which primarily analyzed European economies using data from the pre-Global Financial Crisis (GFC) period, in the following four ways: (i) the sample period is extended to December 2015, thus covering the post-GFC turbulence period (beginning from January 2001); (ii) the model is enriched by considering the People's Republic of China's role in integrating the Asian region through international trade; (iii) the producer price index is included; and (iv) the impact on industrial production is investigated. Using generalized impulse response functions, we examine the impact of a one-time hike in oil and food prices on the general price levels and production for nine Asian countries and 13 other countries, including the United States and the eurozone. We also analyze the differences of shock propagations in the pre- and post-GFC periods. Results indicate that the increased integration and dependence on exports intensified the Asian region's vulnerability to external shocks.
Keywords: C32; E31; F41; F47; O53; 330; Economics; China; People's Republic of; India; Indonesia; Japan; Korea; Republic of; Malaysia; Philippines; Singapore; Thailand